Social support interventions for caregivers of older adults with dementia: a scoping review - Lei Huang; Lin Lin; Juan Lv; Shuai Yuan; Xiao feng Xie; Fengying Zhang; Jiayi Zhu; Lihui Pu; Mengying Qiu; Wenyi Jiang; Liqin Wei (BMJ Open)
Objectives To identify and assess the social support interventions provided to caregivers of older adults with dementia. By synthesising the findings, it seeks to provide insights into effective strategies that can enhance caregivers’ support.Design A scoping review.Data sources The Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews was strictly followed in this study. Searches were systematically conducted across five databases (PubMed, Web of Science, Embase, Cochrane Library, CINAHL) from their inception up to February 2025.Eligibility criteria for selecting studies We included original intervention studies published in English that examined social support interventions for caregivers of older adults with dementia, focusing on outcomes reporting social support.Data extraction and synthesis Data extraction was conducted using a standardised Microsoft Excel chart based on Arksey and O’Malley’s method. Two reviewers independently collected information on study characteristics (authors, country, publication year, design, sample size, assessment tools, interventions and outcomes). Disagreements were resolved by a third independent reviewer.Results A total of 31 studies were selected for this review, revealing six distinct categories of social support interventions for caregivers of older adults with dementia. These categories included peer support (n=7), counselling group intervention (n=2), health education (n=2), mindfulness-based stress reduction intervention (n=1), individual therapy (n=1) and multicomponent interventions (n=18). The findings indicate that these interventions significantly enhanced the social support available to caregivers, leading to positive outcomes such as reduced caregivers burden, anxiety, depression and improved coping skills.Conclusion This review underscores the variety of interventions designed to enhance social support for caregivers of older adults with dementia. The findings provide valuable insights for caregivers, administrators and other stakeholders, emphasising the critical need to adopt and promote effective social support strategies for this population.Trial registration details A review protocol was registered on the OSF（Open Science Framework） registries, with the following registration doi: https://doi.org/10.17605/OSF.IO/D9C53.